2016
DOI: 10.5505/sakaryamedj.2016.16056
|View full text |Cite
|
Sign up to set email alerts
|

The Seasonal Distribution of Appendicitis

Abstract: Amaç Apandisit acil cerrahi müdahale gerektiren nedenlerin başında gelmektedir. Güncel literatürde apandisitin belli mevsimsel dağılımını gösteren çalışmalar mevcuttur. Bu çalışmada Adıyaman ilinde apandisit tanısının mevsimsel dağılımını incelemeyi amaçladık. Gereç ve YöntemlerHastanemizde 2014 yılı içerisinde akut apandisit ön tanısı ile apendektomi yapılan hastalar retrospektif olarak incelendi. Hastalar; yaş, cinsiyet, operasyonu gerçekleştiren klinik, anestezi yöntemi ve operasyonun gerçekleştirildiği mev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…[6] The incidence of AAp greatly varies by country, geographical regions within countries, race, age, sex, socioeconomic status, nutritional habits, hygiene conditions, meteorological events, and seasons. [6,10] Studies have demonstrated that the AAp incidence shows variation by geographical regions. Uludag et al [10] indicated an increase in AAp incidence in high-altitude and cold regions during the winter months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] The incidence of AAp greatly varies by country, geographical regions within countries, race, age, sex, socioeconomic status, nutritional habits, hygiene conditions, meteorological events, and seasons. [6,10] Studies have demonstrated that the AAp incidence shows variation by geographical regions. Uludag et al [10] indicated an increase in AAp incidence in high-altitude and cold regions during the winter months.…”
Section: Discussionmentioning
confidence: 99%
“…[6,10] Studies have demonstrated that the AAp incidence shows variation by geographical regions. Uludag et al [10] indicated an increase in AAp incidence in high-altitude and cold regions during the winter months. In hotter, more humid regions, the incidence was noted to increase in the summer months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of acute appendicitis shows significant changes based on age, sex, geographical region, country, race, socioeconomic status, hygiene, dietary habits, and seasons (8,9). In our series, the highest incidence in all three groups was between the ages of 18-39.…”
Section: Discussionmentioning
confidence: 50%
“…The increase in the incidence of appendicitis in the summer months is said to be affected by the increased risk of gastrointestinal infections, intestinal parasite outbreaks, air pollution exposure, excessive alcohol consumption, and high carbohydrate and low fiber diet. In addition, the effects of touristic migration in the summer are particularly effective in touristic areas (8,9,(19)(20)(21). When we looked at the perforated appendicitis group in our series, the incidence was higher in the summer (41%).…”
Section: Discussionmentioning
confidence: 80%